The influence of caregiver's migration status on child's use of healthcare services: evidence from Ireland. Issue 3 (26th February 2021) - Mohan, Gretta
Abstract: Large‐scale international migration continues apace. From a health‐care services perspective, it is important to understand the influence of migrant heritage on utilization, to allocate resources appropriately and facilitate equity. However, the differences in utilization across different migrant groups remain poorly understood, particularly so for paediatric populations. This paper contributes to filling this gap in knowledge, examining the health‐care contact of children for whom their primary caregiver is foreign‐born, using longitudinal data from two nationally representative surveys. The study setting is Ireland, which provides an interesting case as a small, open European country, which for the first‐time experienced net inward migration in the past two decades. For both cohorts, panel regression models, adjusting for socioeconomic and health indicators, demonstrated lower utilization of general practitioner (GP) services for children of caregivers from 'less‐advanced, non‐Anglosphere, non‐European Union (EU)' nations, relative to native‐born counterparts. Relatively lower attendances at Emergency Departments and hospital nights were also observed for this group, as well as for children born to EU (non‐UK) caregivers. The insights provided are instructive for policymakers for which immigration is a substantial phenomenon in current and future population demographics.